1994
DOI: 10.1084/jem.180.2.687
|View full text |Cite
|
Sign up to set email alerts
|

A natural killer cell receptor specific for a major histocompatibility complex class I molecule.

Abstract: Sllll~mal~Target cell expression of major histocompatibility complex (MHC) class I molecules correlates with resistance to lysis by natural killer (NK) cells. Prior functional studies of the murine NK cell surface molecule, Ly-49, suggested its role in downregulating NK cell cytotoxicity by specifically interacting with target cell H-2D d molecules. . Although the molecular basis for NK cell specificity is poorly understood, target cell susceptibility to spontaneous cytotoxicity is inversely proportional to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(54 citation statements)
references
References 26 publications
2
52
0
Order By: Relevance
“…Also, Ly49A expression on NK cells is modulated in mice expressing H-2D d (21). Physical interaction is supported by studies of Chinese hamster ovary cells transfected with Ly49A that bind H-2D d -transfected C1498 cells (22). The recognition of ␣1/␣2 domain of H-2D d is supported by two lines of indirect evidence.…”
mentioning
confidence: 50%
“…Also, Ly49A expression on NK cells is modulated in mice expressing H-2D d (21). Physical interaction is supported by studies of Chinese hamster ovary cells transfected with Ly49A that bind H-2D d -transfected C1498 cells (22). The recognition of ␣1/␣2 domain of H-2D d is supported by two lines of indirect evidence.…”
mentioning
confidence: 50%
“…Ly-49A binds the class I molecules H-2D d , D k , and D p , and Ly-49G2 binds H-2D d and H-2L d . [37][38][39][40][41] These bindings mediate a negative signal to the NK cells, resulting in inhibition of lysis. Recent studies have suggested that these members of the Ly-49 family may also interact with H-2 b molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory receptors contain an immunoreceptor tyrosine-based inhibitory motif in the cytoplasmic tail that, upon receptor cross-linking, recruits Src homology 2 domaincontaining tyrosine phosphatase-1 and -2 (11)(12)(13)(14). Ly49A is the best characterized member and has been shown to recognize the class I molecules H-2D d , D k , and D p , and binding mediates a negative signal to the NK cell, resulting in inhibition of lysis (15)(16)(17).…”
Section: Mhc Class I-ly49 Interactionsmentioning
confidence: 99%